1998
DOI: 10.1038/31269
|View full text |Cite
|
Sign up to set email alerts
|

Function of the chemokine receptor CXCR4 in haematopoiesis and in cerebellar development

Abstract: Chemokines and their receptors are important in cell migration during inflammation, in the establishment of functional lymphoid microenvironments, and in organogenesis. The chemokine receptor CXCR4 is broadly expressed in cells of both the immune and the central nervous systems and can mediate migration of resting leukocytes and haematopoietic progenitors in response to its ligand, SDF-1. CXCR4 is also a major receptor for strains of human immunodeficiency virus-1 (HIV-1) that arise during progression to immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

42
1,783
5
13

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,305 publications
(1,843 citation statements)
references
References 30 publications
42
1,783
5
13
Order By: Relevance
“…The functions of CXCR4 have not yet been fully understood, but it appears that it mediates a large variety of functions including leukocyte development and trafficking, HIV-infection, correct foetal vascularisation and CNS development and possibly cell division, tumourigenesis and growth (Tachibana et al, 1998;Zou et al, 1998;Gabuzda and Wang, 1999). Rempel et al (2000) observed a tumour grade-dependent surge of CXCR4 mRNA levels in glioblastoma multiforme and that this receptor is mainly expressed in regions of angiogenesis and degenerative, necrotic, and microcystic changes rather than in sections of rapid cell proliferation.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%
“…The functions of CXCR4 have not yet been fully understood, but it appears that it mediates a large variety of functions including leukocyte development and trafficking, HIV-infection, correct foetal vascularisation and CNS development and possibly cell division, tumourigenesis and growth (Tachibana et al, 1998;Zou et al, 1998;Gabuzda and Wang, 1999). Rempel et al (2000) observed a tumour grade-dependent surge of CXCR4 mRNA levels in glioblastoma multiforme and that this receptor is mainly expressed in regions of angiogenesis and degenerative, necrotic, and microcystic changes rather than in sections of rapid cell proliferation.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%
“…Stem cells are believed to reside in close proximity to the endosteal surface of the bone, where osteoblasts are also located 21,22 . Interactions between SDF-1, produced by the osteoblasts 21 , and its receptor, CXCR4, expressed by the stem/progenitor cells 23,24 , is thought to play a major role in stem cell trafficking in embryogenesis 17,24 and in maintaining the stem cells within their niche in the marrow 25,26 . A great deal of evidence indicates that alterations in SDF-1 concentrations in marrow and blood result in stem/progenitor cell mobilization.…”
Section: Introductionmentioning
confidence: 99%
“…CXCR4 is widely expressed on hematopoietic cells, including stem cells, B cells, subsets of T cells, monocytes and neutrophils. It is known to fulfill an important role in hematopoiesis and organogenesis [1,2]. Moreover, CXCR4 has been studied in detail as coreceptor for HIV infection of T cells [3].…”
Section: Introductionmentioning
confidence: 99%